A Guide (not only) for Economics Dictionaries - Caruso, Valeria (HERMES - Journal of Language and Communication in Business, 2014)
The recent report by Besomi (2013) shows the huge number of Economics dictionaries available online, but also describes some of their shortcomings; on the contrary Fuertes-Olivera (2012) points out the potential of these resources in a learning context. However, in order to offer a quick reference guide to Economics dictionaries for web surfers, an evaluation system (Caruso 2011) has been designed to assess dictionary usability with respect to three kinds of prospective users (laymen, semi-experts, and experts), both in cognitive and communicative tasks, and with special reference to two types of situations in which the dictionaries might be consulted, namely translation and learning. This project, however, is not devoted to testing data quality, therefore it doesn’t necessarily give any guarantees to web surfers regarding the contents provided by unrestricted dictionaries found on the Internet. The analysis of Economics dictionaries carried out using this tool, offers a quantitative survey of the overall lexicographical features they display, proving that, even if these resources are on average not particularly suited for communicative tasks, some of them include specific kinds of data that are considered crucial for supporting users in text production (Alonso et al. 2011).